Salivary gland cancers in elderly patients: challenges and therapeutic strategies - Colombo, Elena; Van Lierde, Charlotte; Zlate, Alexandra; Jensen, Alexandra; Gatta, Gemma; Didonè, Fabio; Licitra, Lisa F.; Grégoire, Vincent; Vander Poorten, Vander; Locati, Laura D. (Frontiers in Oncology, 2022)
Salivary gland carcinomas (SGCs) are the most heterogeneous subgroup of head and neck malignant tumors, accounting for more than 20 subtypes. The median age of SGC diagnosis is expected to rise in the following decades, leading to crucial clinical challenges in geriatric oncology. Elderly patients, in comparison with patients aged below 65 years, are generally considered less amenable to receiving state-of-the-art curative treatments for localized disease, such as surgery and radiation/particle therapy. In the advanced setting, chemotherapy regimens are often dampened by the consideration of cardiovascular and renal comorbidities. Nevertheless, the elderly population encompasses a broad spectrum of functionalities. In the last decades, some screening tools (e.g. the G8 questionnaire) have been developed to identify those subjects who should receive a multidimensional geriatric assessment, to answer the question about the feasibility of complex treatments. In the present article, we discuss the most frequent SGC histologies diagnosed in the elderly population and the relative 5-years survival outcomes based on the most recent data from the Surveillance, Epidemiology, and End Results (SEER) Program. Moreover, we review the therapeutic strategies currently available for locoregionally advanced and metastatic disease, taking into account the recent advances in precision oncology. The synergy between the Multidisciplinary Tumor Board and the Geriatrician aims to shape the most appropriate treatment pathway for each elderly patient, focusing on global functionality instead of the sole chronological age.